2021
DOI: 10.34172/ijhpm.2021.53
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors that Promote Low-Value Care: Views of Experts From the United States, Canada, and the Netherlands

Abstract: Background: Around the world, policies and interventions are used to encourage clinicians to reduce low-value care. In order to facilitate this, we need a better understanding of the factors that lead to low-value care. We aimed to identify the key factors affecting low-value care on a national level. In addition, we highlight differences and similarities in three countries. Methods: We performed 18 semi-structured interviews with experts on low-value care from three countries that are actively reducing low-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…To reduce the use of LVC, it is important to understand the factors influencing LVC and to tailor governance strategies to target these factors [11]. A recent study explored key national-level factors that promoted LVC use across three countries (the Netherlands, the United States and Canada) [9]. Our findings of national-level activities used to govern the de-implementation of LVC in Sweden targeted two of these key factors: the pharmaceutical and medical device industry and biased knowledge of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the use of LVC, it is important to understand the factors influencing LVC and to tailor governance strategies to target these factors [11]. A recent study explored key national-level factors that promoted LVC use across three countries (the Netherlands, the United States and Canada) [9]. Our findings of national-level activities used to govern the de-implementation of LVC in Sweden targeted two of these key factors: the pharmaceutical and medical device industry and biased knowledge of care.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of national-level activities used to govern the de-implementation of LVC in Sweden targeted two of these key factors: the pharmaceutical and medical device industry and biased knowledge of care. Verkerk et al [9] describe industry as a powerful actor contributing to LVC by advertising medical products to the population and through their influence on policy-makers and education and research funding. Our results showed that the control of pharmaceutical products, including the withdrawal of unsafe pharmaceutical products, removal of the substitution of medicines and controlling the pricing of products, was used for governing the de-implementation of LVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Money, Finance, and Organisation: Health Coverage, Resource Allocation and the Organisation of Care Delivery, Financing and Configuration of Health Systems, and Integration Across Levels of Care Money, finance, and organisation were major drivers of low-value care in the Lancet Right Care Series 4 but were only briefly touched on by the participants in Verkerk and colleagues study 1 . Inadequate health insurance coverage can prevent people from accessing essential care (eg, if people are uninsured or underinsured, or if a health insurer does not cover a specific service).…”
mentioning
confidence: 99%
“…Power and Human Relationships: Strengths or Weaknesses of the Therapeutic Relationship, Flawed Decision-Making, Contest for Political Control, Political Mobilisation and Demand for Care, Professional Societies and Other Mediators, and Fear of Litigation Fear of litigation was discussed at length in the article by Verkerk and colleagues. 1 Yet, there are other factors related to power and human relationships that can exert their force on the provision of low-value care. The patient-clinician relationship at the point of care is ultimately where low-value care manifests.…”
mentioning
confidence: 99%